2020
DOI: 10.1101/2020.01.06.896548
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracing the evolutionary history and global expansion ofCandida aurisusing population genomic analyses

Abstract: AbstractCandida auris has emerged globally as a multidrug-resistant yeast that can spread via nosocomial transmission. An initial phylogenetic study of isolates from Japan, India, Pakistan, South Africa, and Venezuela revealed four populations (Clades I, II, III, and IV) corresponding to these geographic regions. Since this description, C. auris has been reported in over 30 additional countries. To trace this global emergenc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(100 citation statements)
references
References 49 publications
6
94
0
Order By: Relevance
“…Candida auris is an emerging, drug‐resistant yeast, responsible for hospital outbreaks internationally . First recognised as a new species of Candida in 2009, cases have been reported in over 30 countries, including the United Kingdom and United Arab Emirates . In outbreak settings, bloodstream, urinary tract and deep tissue infections have been reported, in addition to colonisation.…”
Section: Discussionmentioning
confidence: 99%
“…Candida auris is an emerging, drug‐resistant yeast, responsible for hospital outbreaks internationally . First recognised as a new species of Candida in 2009, cases have been reported in over 30 countries, including the United Kingdom and United Arab Emirates . In outbreak settings, bloodstream, urinary tract and deep tissue infections have been reported, in addition to colonisation.…”
Section: Discussionmentioning
confidence: 99%
“…C. auris has not been detected earlier than 2009 by The SENTRY Antifungal Surveillance Program, which has been collecting consecutive invasive Candida isolates from 135 participating medical centers in North America, Europe, Latin America and the Asia-Pacific regions since 1997 (Pfaller et al, 2019). However, molecular clock estimates from 304 worldwide genomes date the most recent common ancestor of each of the four clades within the last 339 years, and outbreak isolates from Clades I, III, and IV to 34-35 years ago (∼10 years prior to first being detected) (Chow et al, 2020). While the details of its origin remain unclear, C. auris is not the only fungal pathogen to have recently clinically emerged.…”
Section: The Emergence Of C Aurismentioning
confidence: 99%
“…This isolate was taken from a patient in 2009 demonstrating independent emergences in 2009 of at least two of the C. auris lineages (Clade II and Clade III). A recent study comparing 204 genomes of C. auris using Bayesian molecular clock phylogenetics estimated the origin of each of the four clades within the last 339 years, and outbreak clusters (Clade I, III, and IV) originating 34-35 years ago (Chow et al, 2020), suggesting more historic samples were not identified.…”
Section: The Emergence Of C Aurismentioning
confidence: 99%
See 2 more Smart Citations